Study of the Formation of Amorphous Carbon and rGO-like Phases from Palmyra Sugar by Variation of Calcination Temperature: Fahmi Astuti, Novita Sari, Vera Laviara Maghfirohtuzzoimah, Retno Asih, Malik Anjelh Baqiya, Darminto Darminto - Fahmi Astuti Fahmi Astuti; Novita Sari Novita Sari; Vera Laviara Maghfirohtuzzoimah Vera Laviara Maghfirohtuzzoimah; Retno Asih Retno Asih; Malik Anjelh Baqiya Malik Anjelh Baqiya; Darminto Darminto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2020)
We have processed biomass from palmyra sugar to produce allotrope carbon by heating process with the variation of calcination temperature. The formation of amorphous carbon (a-C) was confirmed from the XRD result heated at 400°C with the observation of the peak at the position of 24o. By increasing the temperature at 700°C, the presence of two peaks at 24o and 43o were observed, indicating the formation of rGO-like phase. The functional groups detected by FTIR spectra consist of C=C, C-O, C=O, C-H and O-H. The result of conductivity measurement exhibits that the material can be classified as semiconducting materials.